Edge‐Enriched Mo2TiC2Tx/MoS2 Heterostructure with Coupling Interface for Selective NO2 Monitoring (Adv. Funct. Mater. 39/2022). (26th September 2022) - Zhao, Qiuni; Zhou, Wenzhe; Zhang, Mingxiang; Wang, Yang; Duan, Zaihua; Tan, Chaoliang; Liu, Bohao; Ouyang, Fangping; Yuan, Zhen; Tai, Huiling; Jiang, Yadong
Abstract : NO2 Monitoring In article number 2203528, Fangping Ouyang, Zhen Yuan, Huiling Tai, and co‐workers, by combining the strong adsorption of Mo2 TiC2 T x with the edge‐enriched structure of MoS2, propose a Mo2 TiC2 T x /MoS2 heterostructure with a coupling interface to develop a NO2 gas sensor with high selectivity and sensitivity. Moreover, a wireless NO2 gas monitoring system is demonstrated for gas leakage searching and danger warning in unmanned cruises, which expands the application of DTM MXene in sensing systems.